"Cambridge handbook of culture, organizations and work / edited by Ravi S. Bhagat and Richard M. Steers" - "Bhagat, S. Ravi.(ed.)" (Delhi, 2011)
As political, legal, and economic barriers are receding, cultural barriers emerge as a principal challenge to organizational survival and success. This handbook reviews, analyzes, and integrates available theory and research to give the best information possible concerning the role of culture and cultural differences in organizational dynamics.
Keywords: Corporate culture-Cross-cultural studies